Alkitab Sebagai Dasar Utama Guru PAK Dalam Mengajar - Asrinia Susanti Riu; Rounauly Marbun (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The Bible is the main source of knowledge for every believer, especially for children in education. However, there is a tendency that Christian education prioritizes an educational model that emphasizes humanitarian philosophy so that it tends to no longer make the Bible the main source of Christian education. In obtaining data for writing this article, the author used a qualitative method with a literature review approach. The Bible is a material that should be given to children or society. This means that the teaching of the Bible itself does not only talk about the formation of morality and spirituality, but can also give weight to the main source as Christian education. The Bible is used as the main basis for teaching Christian Education in churches and schools that have a Christian curriculum. This is because the Bible is considered a holy book that contains the basic teachings of Christianity and is the highest authority for Christians. Therefore, in teaching Christian Religious Education, a Christian Religious Education teacher is required to use the Bible as the main source in providing explanations and teaching about the teachings of Christianity.